Xi Jinping, China, and the World (Part 1) - EAA Editorial Office (Education About Asia, 2021)
During the last 4-5 years, President Xi Jinping’s government has engaged in aggressive domestic and global policies that raise profound concerns for human rights and freedom. This exclusive focuses upon China’s actions in Hong Kong, Taiwan, and Xinjiang.
Keywords: China; China and Inner Asia; Culture; Education; History; International Relations; Law; Political Science; Taiwan